Enkephalins increase cyclic adenosine monophosphate content, calcium uptake, and contractile state in cultured chick embryo heart cells. - Laurent, S (1986)
Peripheral vascular effects of opioid peptides are well known, but direct myocardial effects have not been established. We studied the inotropic response of spontaneously beating cultured chick embryo ventricular cells to the enkephalin analogue [D-Ala2]-enkephalin. Amplitude of cell motion increased in a concentration-dependent manner with 0.53 microM [D-Ala2]-enkephalin producing half-maximal response. The mechanism of this positive inotropic effect was investigated by examining alterations in 45Ca influx, cyclic AMP accumulation and adenylate cyclase activity in response to [D-Ala2]-enkephalin. At maximally inotropic concentrations, the 45Ca influx rate increased 39%, adenylate cyclase was stimulated by 30%, and cyclic AMP content rose more than twofold. Thus, in contrast to neural tissue, receptors for enkephalin in cultured heart cells are coupled to adenylate cyclase in a stimulatory manner. Occupancy of these receptors produces an increase in cyclic AMP levels and exerts a positive inotropic effect via a verapamil-sensitive enhancement of Ca influx.